Decolourisation Of Rayon Effluents And Bleaching Of Kraft Pulp By Stereum Ostrea - G.RAMA KRISHNA; S.V.S.S.S.L.HIMA BINDU N; M. A. SINGARA CHARYA (International Journal of Pharma and Bio Sciences, 2011)
A potential lignolytic fungus, Stereum ostrea was analysed for the decolourisation of industrial effluents discharged from rayon pulp mills. The colour removal was from 5580.85 to 2690.05 CU during 40 days of incubation time. The laccase activity during the decolorization process was increased up to 20th day (862.77 U/L) and after that it was very low. Chemical bleaching was effective and showed 92-94% of brightness with viscosity 14 cp, while biobleaching of pulp recorded 78% of brightness with 4 cp viscosity during 40 days of solid state fermentation. The rayon sheet, after biobleaching was prepared and 76% brightness and 8 cp viscosity was noticed, which was accepted with moderate response in industries.